NALISIS EFISIENSI FAKTOR – FAKTOR PRODUKSI USAHATANI PADI ORGANIK DENGAN PADI ANORGANIK DI DESA SUMBER NGEPOH KECAMATAN LAWANG KABUPATEN MALANG - Saragih, Febrina Lestari; Indah, Pawana Nur; Widayanti, Sri (Berkala Ilmiah AGRIDEVINA, 2017)
Research place selection was determined purposively (purposive sampling) byconsideration that Sumber Ngepoh Village is one of the organic rice production centre inLawang Subdistrict Malang Regency. This research was aimed to analyze the activity oforganic and anorganic rice farming, to compare organic and anorganic farmingproduction, also to compare cost and income on organic and anorganic rice farming inSumber Ngepoh Village. The variables on organic rice farming which was affectedsignificantly were land area, labour, seeds, fertilizer, and pesticide. Whereas, Thevariables on anorganic rice farming which was affected significantly were land area,labour, seedes, and pesticide. While fertilizer affected unsignificant. The total cost oforganic rice farming production per hectare was Rp. 460.525.000 by the average amountwas Rp. 12.446.621 per hectare. The total income of an organic rice farming per hectarewas Rp 29.519.189 by the average amount was Rp 17.072.567 and total value of B/Cratio was 70,27 by the average amount was 1,89 per hectare. The total cost of anorganicrice farming production per hectare was Rp. 263.537.500 by the average amount was Rp12.494.630 per hectare. The total income of anorganic rice farming per hectare wasRp182.292.500 by the average amount was Rp 7.925.760 and total value of B/C ratio was21.00 by the average amount was 0,91 per hectare.